A novel and clean utilization of multiple solid wastes to produce foam glass-ceramic. (17th March 2023) - Wang, Hao; Chen, Ziwei; Meng, Zhao; Liu, Lili; Wang, Xidong; Qian, Dayi; Xing, Yi
Graphical abstract: Highlights: Foam glass–ceramic with good performance was developed by multiple solid wastes. Desulphurisation gypsum was used as foaming agent in this study. The results show that the use of material prepared in this study is safe for the environment. Abstract: Direct materialisation is a large-scale solid waste utilisation approach with economic and environmental benefits. This study explored a novel process for the utilisation of multiple solid wastes, including fly ash, blast furnace slag and desulphurisation gypsum, for foam glass–ceramic preparation. The high-temperature decomposition reactions of desulphurisation gypsum were analysed to investigate its suitability as a foaming agent. The effects of the sintering temperature during the preparation process and the raw material composition on the properties of the prepared foam glass–ceramic were investigated. The optimum parameters were a desulphurisation gypsum addition amount of 7 wt% and a sintering temperature of 1, 200 °C, while the corresponding bulk density, thermal conductivity and compressive strength were 1.21 g/cm 3, 0.153 W/m K and 11.23 MPa, respectively. Finally, the migration and transformation of heavy metals during the preparation process and the leaching behaviour of heavy metals from the final material were analysed. The recycling of multiple solid wastes for foam glass–ceramic production has significant economic and environmental benefits. The excellent thermal insulation and strength properties of foam glass–ceramic make them suitable for manufacturing wall insulation materials.